Determinantes da anemia em gestantes usuárias do Programa de Saúde da Família do município de Santo Antônio de Jesus - Bahia - Silva, Renata Marques da (2015)
During pregnancy, the occurrence of anemia is high due to the physiological changes to which a woman's body is subjected during fetal development. Even before the institution of the treatment protocol that the Ministry of Health recommended, the maintenance of high levels of prevalence of anemia during pregnancy was observed. Other causal factors still unknown, beyond those already investigated classics, are possibly contributing to this occurrence. OBJECTIVE: To identify socioeconomic, demographic, nutritional, and gynecological-obstetric factors associated with anemia as well as estimate the frequency of different types and levels of severity of anemia in pregnant women. METHOD: This is a cross-sectional study conducted with pregnant women who received prenatal care in the Family Health Units in Santo Antônio de Jesus in Bahia. Patients were classified as being diagnosed with anemia or not, according to the World Health Organization (WHO) criteria that consider the value of hemoglobin less than 11 g / dL. Was also performed to diagnose the types of anemia (pernicious, chronic disease, and iron deficiency) and assessment of the severity of anemia (mild, moderate, and severe). Data collection included the application of a questionnaire in which socioeconomic and demographic information was obtained along with reproductive and pregnancy information, and blood collection was also completed for the determination of haematological parameters. Data were analyzed using Stata, version 11, in which the frequency of different types of anemia was estimated and the association between the studied variables and the presence of anemia was assessed by estimating the prevalence ratio (PR), with its respective confidence interval (CI) of 95% and statistical significance level of 5%. RESULTS: They are presented in a scientific paper, "Determinants of Anemia in Pregnant Women Using the Health Family Program," to be submitted to the Portuguese Journal of Public Health. The final sample consisted of 349 pregnant women, and after the regression analysis model was used, the prevalence ratios—both as adjusted gross—found no statistically significant association between the selected features and the main outcome. The prevalence of anemia in the study sample was 22.64%, classified as moderate in Portuguese Journal of Public Health. CONCLUSIONS: No association was found between the investigated factors and anemia. In addition, the most common form of the disease was the anemia of chronic disease, with there being a low prevalence of iron deficiency anemia. Thus, the need exists to investigate other factors besides iron deficiency as well as examine therapeutic strategies targeting anemia in pregnant women, which are more effective than those existing in the health actions aimed at this group.